Modal Psikologis dan Hubungan Atasan–Bawahan dengan Keterikatan Kerja di Organisasi AIESEC Universitas Sebelas Maret - Dinda Naila Ayendra; Aditya Nanda Priyatama (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
Studies on work engagement among members of not-for-profit student organizations are still limited. To maximize the effectiveness of the organization, further studies are needed on the factors that make members of the organization more engaged in their work. This study aims to examine the correlational relationship between psychological capital and leader-member exchange on the work engagement of AIESEC Universitas Sebelas Maret local committee members. This research is a quantitative correlational study involving all AIESEC members at Universitas Sebelas Maret. The results of this study indicate that psychological capital and leader-member exchange simultaneously have a strong positive relationship with work engagement. It is advised that organizations develop strategies to cultivate members’ psychological capital and ensure good quality relationships between team members and their direct team leaders to keep them engaged in their work.